2009
DOI: 10.1111/j.1440-1754.2009.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching paediatric epilepsy to medical students: A randomised crossover trial

Abstract: This is the first randomised crossover trial evaluating the teaching of clinical reasoning in comparative medical education research. Interactive lecturing and computerised tutorial were both effective in teaching observational skills and clinical reasoning. Interactive lecture is the preferred method, and may influence initial engagement in learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Of the 48 papers reviewed, 24 reported on empirical studies in which a particular approach was examined . Fourteen articles were descriptive in nature, offering only a portrayal of a particular approach to the teaching of CR …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 48 papers reviewed, 24 reported on empirical studies in which a particular approach was examined . Fourteen articles were descriptive in nature, offering only a portrayal of a particular approach to the teaching of CR …”
Section: Resultsmentioning
confidence: 99%
“…In 12 of the 48 papers reviewed, the approach taken to the teaching of CR involved having students diagnose clinical cases, the descriptions of which already contained all the patient's essential features . (Nendaz et al .…”
Section: Resultsmentioning
confidence: 99%
“…The lack of use of PNES videos may be due to ethical concerns on posting these videos on the web. A related method is computerised tutorials, but these methods have not been designed to aid visual diagnosis of ES and PNES 26 27…”
Section: Discussionmentioning
confidence: 99%
“…Reaction evaluations, assessments, behavioural change and clinical outcomes of educational interventions were limited; only 16 randomized controlled trials were identified (Table ) that attained level 2 evidence . A Kirkpatrick evaluation or reaction was recorded in eight of 16 studies (50%), a learning outcome assessment was performed in 15 of 16 studies (94%), a behavioural change was measured in just two of the 16 studies (12%) and one (6%) assessed a clinical result or outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors identified nine randomized trials and concluded that overall the studies failed to embrace but 'the most basic outcome measures' and that there was 'a need for increased rigour in medical educational studies'. were identified (Table 1) that attained level 2 evidence [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. A Kirkpatrick evaluation or reaction was recorded in eight of 16 studies (50%), a learning outcome assessment was performed in 15 of 16 studies (94%), a behavioural change was measured in just two of the 16 studies (12%) and one (6%) assessed a clinical result or outcome ( Table 2).…”
Section: Systematic Review (Cebm Level 1)mentioning
confidence: 99%